2020
DOI: 10.1158/1078-0432.ccr-20-3345
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Copy-number Alterations in Circulating Tumor DNA as a Novel Biomarker for Patients with High-grade Serous Ovarian Cancer

Abstract: Purpose: High-grade serous epithelial ovarian cancer (HGS-EOC) is defined by high levels of somatic copy-number alterations (SCNA) with marked spatial and temporal tumor heterogeneity. Biomarkers serving to monitor drug response and detect disease recurrence are lacking, a fact which reflects an unmet clinical need. Experimental Design: A total of 185 plasma samples and 109 matched tumor biopsies were collected from 46 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…In agreement, we more recently showed that FOXM1 copy number correlates with FOXM1 mRNA and protein expression in pan-cancer [ 27 ]. The 12p13.33 amplifications were reported to be common in an independent cohort of HGSC patients before and after front-line chemotherapy (and detectable in plasma), further supporting this mechanism [ 128 ]. Despite the high frequency of FOXM1 SCNA observed in HGSC, an even greater proportion of tumors show FOXM1 overexpression or pathway activation (reaching ~90% of HGSC cases) [ 30 , 127 ], indicating that additional mechanisms contribute to FOXM1 overexpression and pathway activation in HGSC.…”
Section: Foxm1 Is Overexpressed and Activated In Ovarian Cancermentioning
confidence: 86%
See 1 more Smart Citation
“…In agreement, we more recently showed that FOXM1 copy number correlates with FOXM1 mRNA and protein expression in pan-cancer [ 27 ]. The 12p13.33 amplifications were reported to be common in an independent cohort of HGSC patients before and after front-line chemotherapy (and detectable in plasma), further supporting this mechanism [ 128 ]. Despite the high frequency of FOXM1 SCNA observed in HGSC, an even greater proportion of tumors show FOXM1 overexpression or pathway activation (reaching ~90% of HGSC cases) [ 30 , 127 ], indicating that additional mechanisms contribute to FOXM1 overexpression and pathway activation in HGSC.…”
Section: Foxm1 Is Overexpressed and Activated In Ovarian Cancermentioning
confidence: 86%
“…In HGSC patients, shallow whole genome sequencing (sWGS) of circulating tumor DNA (ctDNA) from plasma revealed a 16% increase in chromosome 12p13.33 amplification (location of FOXM1 ) after the acquisition of chemotherapy resistance [ 128 ]. In agreement, we observed that almost half of HGSC patients have increased FOXM1 expression in recurrent chemoresistant tumors [ 256 ].…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
“…36,37 Lowcoverage WGS of cfDNA has been used to characterize CNAs in many cancers including TNBC, and the burden of CNAs may be prognostic. 7,[38][39][40][41][42][43][44][45] In some cancers, CNA burden may be predictive of response to checkpoint inhibitors. 46,47 But, to our knowledge, no previous study has associated a focal CNA detected by ctDNA ULP-WGS with response to a particular therapy for any cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic heterogeneity of relapse disease was reduced after pt treatment, with the emergence of newly frequent cytobands that could be involved in t resistance. While this represents a proof-of-principle study performed in a small cohort of patients (n = 46) and lack of an independent clinical validation set, it provides evidence that the low-pass shallow whole-genome sequencing in cfDNA is an inexpensive and useful tool to monitor disease evolution and to anticipate relapse better than the routine clinical biomarkers [ 61 ].…”
Section: Ctdna Analysis: the State Of The Art For Ovarian Cancermentioning
confidence: 99%